An amplitude detector for variable frequency sinusoidal signals - Raksachat, Pariwat; Chaikla, Amphawan; Kaewpoonsuk, Anucha; Riewruja, Vanchai; Julsereewong, Prasit (My University, 2006)
In this paper, a JK-flip-flop-based logic circuit is described. Using two output signals of this designed logic circuit to control a buffered peak detector followed by a simple sample-and-hold circuit in sequential operation, a sinusoidal amplitude detector is proposed. The proposed detector allows the frequency of input signals to be varied over a wide range. Experimental results verifying the performances of the proposed circuit are in close agreement with the expected values. © 2006 ICASE.
Keywords: Amplitude detector; Peak detector; Sample-and-hold circuit